The builder the the Kabbah - Khan, Saniyasnain (Goodword Books: New Dehli, 2002)
The story narrates how Prophet Ibrahim and his son Prophet Ismail were commanded by Allah to build the Ka'bah, the sacred house of worship in Makkah. Despite the challenges they faced, including the harsh desert environment, they faithfully followed Allah's command. The book emphasizes themes of faith, obedience, and the importance of following Allah's guidance.